Matthew - Bergh, Regardt Vanden; Robertson, Charles K.; Marcarelly, Robert; Keley, Richard (Dallas, Tex : Visual Bible, 1997)
Special features: search by event (99 events); search by chapter; biographies of Jesus, Matthew, Peter, John the Baptist, Herod II, and Pontius Pilate; music soundtrack.
Viodeorecording
"The only dramatization using the actual scriptures ... word for word from the New International version."
Special features: search by event (99 events); search by chapter; biographies; music soundtrack.
Director of photography, Tobie Swanepoel, Mike Ferris ; editor, Ronnelle Loots ; music by Sue Grealy ; sound facilities, Chris Fellows Sound Studios ; music recorded at Bop Recording Studios ; conductor, Peter Jaspan ; orchestra, members of the NSO and PACT orchestras ; orchestra leader, Denise Sutton ; choir, members of the SABC Chamber Choir ; DVD producer, Charles Bush, III ; executive producer, Charles K. Robertson.
Richard Kiley (Matthew) ; Matthew Roberts (young Matthew) ; Bruce Marchiano (Jesus) ; Gerrit Schoonhoven (Peter) ; David Minnaar (Judas) ; Kevin Smith (John the Beloved) ; Hannes Muller (Andrew) ; Charlton George (James) ; Ivan D. Lucas (Phillip) ; Jacques de Klerk (Bartholomew) ; Sean Michaels (Thomas) ; Tony Joubert (James Alpheus) ; Darryl Fuchs (Simon the Zealot) ; Jonathan Pinnaar (Thaddeus) ; Patrick Mynhart (Herod, Senior) ; Chris Truter (Herod, Junior) ; Joanna Weinberg (Mary) ; Tony Caprari (Joseph) ; Marcel van Heerden (John the Baptist) ; Gordon van Rooyen (Caiaphas) ; Brian O'Shaughnessy (Pontius Pilate) ; Pippa Duffy (Mary Magdalene) ; Dominique Newman (young woman) ; David Muller (Pharisee).
Keywords: Bible.N.T. -- Matthew; Jesus Christ -- Drama; Bible -- Biography